Energy Band Diagram of FTO/porous Silicon Heterostructure. Issue 1 (March 2021) - Hadi, Hasan A.; Ismail, Raid A.
Abstract: We have proposed for the first time the energy band diagram of fluorine doped tin oxide FTO/porous silicon PSi/n-Si heterostructure prepared by spray pyrolysis technique and laser assist-electrochemical etching ECE. The band line-up of the heterojunction was constructed from the electrical and optical properties of FTO and porous silicon. The electrical current-voltage and capacitance-voltage measurements showed the barrier height, ideality factor and built in voltage of the heterojunction were 1.4, 0.69 V and 0.70 V, respectively. The optical energy gap and the average of the optical transmittance of FTO film were 3.6 eV and 78% respectively. The morphology of porous silicon PSi and FTO film investigated by scanning electron microscope SEM. The elemental composition of FTO film was determined using energy dispersive x-ray.